Structural behaviour of the aluminium alloy Temcor joints and Box-I section hybrid gusset joints under combined bending and shear. (15th December 2021) - Zhang, Ying; Wang, Yuanqing; Li, Beibei; Wang, Zhongxing; Liu, Xiaochen; Zhang, Junguang; Ouyang, Yuanwen
Highlights: Results of experimental study on aluminium alloy gusset joints presented. FE models validated against test results. A novel Box-I section hybrid gusset joint system suggested. Three-stage model and R-O model for design of M - Φ curves revised and proposed. Design method for ultimate resistance of the gusset joints connected by swage-locking pins evaluated. Abstract: The structural performance of traditional aluminium alloy Temcor (TAAT) joints and novel Box-I section hybrid gusset (ABI) joints connected by swage-locking pins are investigated under combined bending and shear. The test parameters include gusset joint type and testing programme. The failure modes, stress distributions, moment-rotation responses, initial stiffness and ultimate resistance were reported. The experimental results showed that ABI joints exhibited good characteristics in the load-carrying and rotation capacities. The simplification of testing programme for ABI joints would overestimate the moment and rotation capacities of the gusset joints. The three-stage model and Ramberg-Osgood model of M-Φ curves were revised and suggested to predict the rotational performance of the gusset joints. Furthermore, the design method for the ultimate moment resistance of the gusset joints associated with fracture failure modes was proposed and verified by the test results. The study shows that the novel Box-I section hybrid gusset (ABI) joints connected by swage-locking pins has good potential for application in aluminium alloy spatial reticulated structures.